Integration of Baduy Ecological Philosophy and Environmental Stewardship as a Model of Sustainable Environmental Ethics in Christian Education - Amirrudin Zalukhu (ARUMBAE: Jurnal Ilmiah Teologi dan Studi Agama, 2025)
The Baduy community upholds an ecological philosophy that emphasizes harmony with nature, reflected in their prohibitions against excessive exploitation and their respect for maintaining a balance in the ecosystem. This principle aligns with the concept of environmental stewardship in Genesis 1:26-28, which underscores humanity’s responsibility to manage the earth wisely. Integrating these two perspectives can serve as a model for sustainable ecological ethics in Christian education. This study employs a theological and ethnographic approach to explore the alignment between Baduy ecological wisdom and biblical principles. The findings reveal that this model can enrich Christian education by fostering an eco-theological awareness that balances dominion over creation with responsibility for it. By adopting Baduy sustainability principles, Christian education can promote a more inclusive and contextually relevant ecological mindset among learners. This integration offers an ethical solution to the environmental crisis, emphasizing that Christian faith must be manifested in sustainable ecological practices.